Magnesium Hydroxide Microparticle Treatment Potently Inhibits Venturia oleaginea Pathogenesis on Olives - Aggeliki Andreadelli; Arthur Fau; Antiopi Tsoureki; Elisavet Papa; Katerina Pliatsika; Spyros Petrakis; Penelope Baltzopoulou; Chrysa Pagkoura; Andreas Giannopoulos; George Karagiannakis; Antonios M. Makris (International Journal of Plant Biology)
Olive trees worldwide suffer from a number of devastating fungal diseases that affect production. One such serious disease is olive leaf spot caused by Venturia oleaginea. Recently, we applied magnesium hydroxide porous micron-scale particles (PMPs) on tomatoes and observed potent antimicrobial activity, reducing the fungal load of the treated phyllosphere. To assess the effectiveness of the compound on olive fungal disease, we applied it for two consecutive seasons. One particular olive tree exhibited extreme manifestations of fungal disease and was destined for removal. A single application of Mg(OH)2 PMP reversed all symptoms of the disease and eliminated the Venturia pathogen, curing the tree of disease. Venturia oleaginea appears to be exceptionally susceptible to treatment compared to other species in the fungal leaf community. The beneficial fungus Aureobasidium pullulans increased in relative abundance in all the sprayed trees. No toxicity and leaf loss were observed, and the compound retention exceeded 47 days. All trees sprayed showed drastic reductions in the total fungal load and compared favorably to the commercial copper compound. Spraying induced a moderate expression of key indicator genes associated with stress responses. No leaf chlorosis or shedding were observed. Overall, Mg(OH)2 PMP treatment appears to be a highly promising tool for combating plant fungal disease.